Host Defenses in Murine Malaria: Immunological Characteristics of a Protracted State of Immunity to Plasmodium yoelii - Murphy, James R. (1980)
Random-bred ICR mice recovered from infection with avirulent Plasmodium yoelii were challenged at various later times with virulent P. yoelii or with another species of Plasmodium, P. berghei, to characterize the immunological nature of the long-term state of immunity generated in response to the avirulent infection. It was found that recovered mice resisted lethal challenge with virulent P. yoelii through at least 416 days after primary infection. However, the quality of this immunity changed as the time after avirulent infection increased. Mice challenged early after recovery were able to prevent the development of patent parasitemia. Later, these immune animals lost this capacity and after challenge infections progressed to patency at the same rate as did nonimmune controls. However, after the establishment of parasitemia, those animals which had encountered the homologous parasite a long time before controlled, and then eliminated, blood infection and survived. The “early” state of immunity was expressed by animals which may have harbored small numbers of viable avirulent parasites and possessed a protective humoral factor which could passively transfer anti-P. yoelii activity to naive recipients. In contrast, animals with “late” immunity showed evidence of neither persisting avirulent parasites nor serum anti-P. yoelii activity. The results support the proposition that immunity to this parasite exists as two distinct but interrelated states of immunological reactivity: an early “active” immunity and a later state which has characteristics suggestive of a state of immunological memory wherewith the animals were capable of anamnestically responding to P. yoelii challenge. Little evidence of heterologous immunity to P. berghei was observed for animals recovered from P. yoelii.